Quantitative variability for lesion size and lesion number as components of resistance against Alternaria brassicae in Rapeseed-M ustard - and S.C. CHATTERJEE, RAJBIR YADAV*, S.S. MEENA (Indian Phytopathology, 2008)
Alternaria blight is the most important disease of rapeseed-mustard causing losses every year. All India Coordinated Programme on Rapeseed -Mustard have listed a large number of donor lines on the basis of multi-location testing. However, their utilization in the breeding programme could not lead to the development of a resistant variety. A study was undertaken to quantify the resistance of entries identified on the basis of lesion lesion size and number. Eleven entries with differential response because of number of lesion or size were identified on the basis of two year data. A breeding programme has been proposed to combine them into single background to enhance genetically the level of resistance against Alternaria blight.